2015
DOI: 10.1007/s12178-015-9310-y
|View full text |Cite
|
Sign up to set email alerts
|

Rank ligand as a target in musculoskeletal neoplasms

Abstract: Receptor activator of nuclear factor-κB ligand (RANKL) is a tumor necrosis factor (TNF) family member, which signals through the osteoclast surface RANK. As such, RANKL is required for osteoclast differentiation and function, namely bone resorption. There is now growing evidence that RANKL is a therapeutic target for musculoskeletal neoplasms, namely giant cell tumor of bone (GCTB) and osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“… 1 More recently, denosumab (Ranmark; Daiichi Sankyo Company, Ltd., Tokyo, Japan) has been approved to treat GCTB. 2 Denosumab is a human monoclonal antibody that targets the receptor activator of nuclear factor-κB ligand (RANKL) with high specificity and affinity. 3 Receptor activator of nuclear factor kappa-Β ligand is a signaling molecule that is required for the bone resorptive function of osteoclast-like cells and is highly expressed on the stromal cells of tumors.…”
Section: Introductionmentioning
confidence: 99%
“… 1 More recently, denosumab (Ranmark; Daiichi Sankyo Company, Ltd., Tokyo, Japan) has been approved to treat GCTB. 2 Denosumab is a human monoclonal antibody that targets the receptor activator of nuclear factor-κB ligand (RANKL) with high specificity and affinity. 3 Receptor activator of nuclear factor kappa-Β ligand is a signaling molecule that is required for the bone resorptive function of osteoclast-like cells and is highly expressed on the stromal cells of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, drugs that target osteoclast formation can prevent osteolytic diseases. The RANKL signaling pathway is crucial for osteoclast formation and is an important druggable target for developing therapeutics against pathological diseases of bone loss (Cote 2015, Tat et al, 2009, McGrath 2011. In this study, we found that geraniol significantly alleviated the RANKL-induced osteoclast differentiation of RAW264.7 macrophages and CD14+ monocytes.…”
Section: Discussionmentioning
confidence: 52%
“…Two key osteoclastic factors suggested to be responsible for the progression of tumor-induced osteolysis are: receptor activator of nuclear factor kappa-Β (RANKL) and monocyte chemoattractant protein-1 (MCP-1) [18,19]. A clinical study reported that elevated RANKL expression in biopsies taken from patients with localized, high-grade OS is correlated with poorer prognosis and lower chance of survival [20].…”
Section: Introductionmentioning
confidence: 99%